Proposta de um método de teste para processos de desenvolvimento de software usando o paradigma orientado a notificações - Kossoski, Clayton (2015)
The Notification Oriented Paradigm (NOP) is an alternative to the development of software applications and proposes to solve certain problems in the usual programming paradigms, including the Declarative Paradigm (DP) and Imperative Paradigm (IP). Indeed, the NOP unifies the main advantages of DP and IP while solving (in terms of model) several of its deficiencies and inconveniences related to logical-causal calculation, apparently from both mono and multiprocessor environments. The NOP has been materialized in terms of programming and modeling, but still did not have a formalized method to guide developers in designing and software testing activity. This dissertation proposes a test method for software projects that use the NOP in its development. The proposed software testing method was developed for use in the phases of unit testing and integration testing. The unit testing considers the smallest testable entities of the NOP and requires specific techniques for generating test cases. The integration testing considers the operation of the PON entities together to carry out use cases and can be accomplished in two steps: (1) test on the features described in the requirements and use case and (2) test that directly exercise the NOP entities that make up the use case (as Premisses, Conditions and Rules). The test method was applied in a case study involving the modeling and development of a simple air combat and the results of this research show that the proposed method has great importance in testing NOP programs in both unit and integration testing.